Environmental concern, knowledge, and the enactment of environmental citizenship in a retail food environment: an investigation into the perceptions and behaviours of Cape Town consumers - Ractliffe, Tamzin Pascoe (Department of Environmental and Geographical Science, 2016)
Sustainable consumption has long been recognised as essential for the achievement of sustainable development. Whilst early efforts to achieve sustainable consumption focused on using technological innovation and process efficiencies to reduce the resource intensity of products, create new, less toxic, more environmentally friendly products, and/or improve the efficiency of production processes, the inadequacy of production-based approaches alone has been widely accepted. More recent efforts to achieve sustainable consumption have highlighted that a change in the behaviour of individuals is a prerequisite for its achievement. A significant body of research has focusing on trying to understand the determinants of pro-environmental behaviour and specifically the intersection of environmental concern and environmental knowledge in the manifestation in pro-environmental behaviour. The relatively recent concept of environmental citizenship, premised on the existence of concern and knowledge, and rooted in issues of environmental and social justice, has gained traction as an alternative means by which to achieve both sustainable development and sustainable consumption. This dissertation presents research findings from a mixed-method empirical study of the food consumption behaviour of a purposive sample of upper middle income South African retail food consumers. Applying the notion of environmental citizenship, it considers the influence of critical variables widely identified as key to the expression of pro-environmental behaviour, viz. desire to act, knowledge to act, and ability to act. Specifically it considers the relationship between environmental knowledge, environmental concern and pro-environmental behaviour, as well as the barriers and situational factors in the food retail environment which are reported to inhibit the practice of sustainable consumption behaviour. It then considers whether improvements in objective knowledge have an impact on the enactment of environmental citizenship through an increase in pro-environmental behaviour practices. The main conclusion drawn from the findings of this dissertation is that environmental concern and knowledge are positive predictors of pro-environmental behaviour. However, a low incidence of pro-environmental behaviour was evident in the study sample overall. This is most likely as a result of low levels of environmental concern and general lack of objective knowledge although a significant additional barrier could be the lack of a mature market for sustainable food in South Africa. In keeping with international studies, health concerns appear to be both most prevalent and most influential in determining the practice of pro-environmental behaviours. The study also suggests that efforts to increase levels of objective knowledge may have an impact on the practice of sustainable food consumption behaviours.